Conquest, tribute, and trade: the quest for precious metals and the birth of globalization - Erlichman, Howard J. (Prometheus Books, 2010)
The Portuguese head east -- The Spanish head west -- Convergence with the House of Habsburg -- The great American treasure hunts -- An unlikely bankruptcy -- Mining revolution in Spanish America -- Cash flow squeeze in the Spanish Netherlands -- Convergence in the Far East -- Unimaginable wealth and squander -- The Dutch advance -- Capital of the world